2018
DOI: 10.1002/1873-3468.13124
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli tRNA 2‐selenouridine synthase (SelU) converts S2U‐RNA to Se2U‐RNA via S‐geranylated‐intermediate

Abstract: To date the only tRNAs containing nucleosides modified with a selenium (5-carboxymethylaminomethyl-2-selenouridine and 5-methylaminomethyl-2-selenouridine) have been found in bacteria. By using tRNA anticodon-stem-loop fragments containing S2U, Se2U, or geS2U, we found that in vitro tRNA 2-selenouridine synthase (SelU) converts S2U-RNA to Se2U-RNA in a two-step process involving S2U-RNA geranylation (with ppGe) and subsequent selenation of the resulting geS2U-RNA (with SePO ). No 'direct' S2U-RNA→Se2U-RNA repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
1
33
1
Order By: Relevance
“…Electrostatic potential energy maps illustrating the charge distributions in the mnm5Se2U base analyzed by quantum chemical calculations were drawn up for three the most stable tautomeric forms of the m1mnm5Se2Ura model, i.e., K, E4, and E2, protonated at the amino alkyl residue; these are shown in Figure S31. The data presented for tautomers of m1mnm5Se2Ura were similar to those presented for m1mnm5S2Ura and m1mnm5Ura [25], demonstrating that in the zwitterionic tautomeric structure, the electron-deficient region is located in the vicinity of the ammonium cation at the side chain, while the electron-rich region is dispersed over the Se2 . .…”
Section: Figuresupporting
confidence: 75%
See 3 more Smart Citations
“…Electrostatic potential energy maps illustrating the charge distributions in the mnm5Se2U base analyzed by quantum chemical calculations were drawn up for three the most stable tautomeric forms of the m1mnm5Se2Ura model, i.e., K, E4, and E2, protonated at the amino alkyl residue; these are shown in Figure S31. The data presented for tautomers of m1mnm5Se2Ura were similar to those presented for m1mnm5S2Ura and m1mnm5Ura [25], demonstrating that in the zwitterionic tautomeric structure, the electron-deficient region is located in the vicinity of the ammonium cation at the side chain, while the electron-rich region is dispersed over the Se2 . .…”
Section: Figuresupporting
confidence: 75%
“…As noted recently, tRNA 2-selenouridine synthase SelU, i.e., the enzyme responsible for S→Se replacement, also catalyzes the S-geranylation of 2-thiouridine in tRNAs. Contrary to earlier suggestions, it was recently demonstrated that S-geranylated tRNA primarily acts as the intermediate in S2U-tRNA→Se2U-tRNA transformation [24,25] and does not seem to serve as an amino acid carrier at the ribosome or bind to bacterial cell membranes [21,23,26].…”
Section: Introductioncontrasting
confidence: 64%
See 2 more Smart Citations
“…se 2 U34 is synthesized from s 2 U34 via geranylated intermediate (ges 2 U) by SelU (YbbB) ( Chen et al, 2005 ; Dumelin et al, 2012 ; Sierant et al, 2018b ). Desulfuration activity of 2-thiouracil by DUF523 domain protein in the cell has recently been reported ( Aucynaite et al, 2018 ).…”
Section: Biosynthetic Pathways For Sulfur Modifications In Trnasmentioning
confidence: 99%